Designing Dubbing Time For Students’ Speaking Ability - Iin Baroroh Ma'arif; Mia Oktaviana; Ulfa Wulan Agustina (Universitas KH. A. Wahab Hasbullah, 2018)
Educational system in Indonesia also consist of two types; they are formal and informal education. Formal education is based on the classroom, also using syllaby, and structured. While informal education is based on a learning community, like a course. Informal education do not need formal curriculum or syllaby, they usually make the curriculum by them selves. The example of informal education are TPQ, The researcher investigate students’ speaking ability by using Dubbing Time, to know students ability in speaking ability. In this research, researcher make a fun method learning to improve the students’ ability in speaking skill by using this media. Researcher designed a media by named Dubbing Time. Dubbing Time is one of some media to make a fun learning. Dubbing Time is a media to improve speaking skill for students. In this media, students explain a picture on the screen. This media can use be used in some text such as narrative, descriptive or procedure, but in this case the researcher use narrative text to this research.. The result of media validation is 68 score in good category. The result of material validation is 65 in a good category The result of user validation in get 90,25 score in field study.